Determinants of SARS-CoV-2 Contagiousness in Household Contacts of Symptomatic Adult Index Cases - Trunfio, Mattia; Richiardi, Lorenzo; Alladio, Francesca; Staffilano, Elena; Longo, Bianca; Venuti, Francesco; Ghisetti, Valeria; Burdino, Elisa; Bonora, Stefano; Vineis, Paolo; Di Perri, Giovanni; Calcagno, Andrea (Frontiers in Microbiology, 2022)
Background: Identifying determinants of SARS-CoV-2 transmission in settings of contagion is fundamental to inform containment strategies. We assessed whether SARS-CoV-2 cycle threshold value (Ct) from the first diagnostic nasal-pharyngeal swab of symptomatic index cases and which demographic or clinical characteristics among cases and contacts are associateds with transmission risk within households. Methods: Retrospective prevalence study on secondary SARS-CoV-2 cases (SC) among the household contacts of symptomatic adult index cases randomly sampled from all the SARS-CoV-2-positive diagnostic nasopharyngeal swabs analysed at our regional referral hospital (Amedeo di Savoia Hospital, Turin, Italy) in March 2020. Index underwent a telephone survey to collect their demographic and clinical data and of all their household contacts. The Ct value of RdRp gene from the first diagnostic swab of index cases was recorded and index grouped according to Ct tertiles (A